2000
DOI: 10.1007/pl00011172
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/Antioxidant Status of the Erythrocytes from Patients with Rheumatoid Arthritis

Abstract: It has been suggested that enzymatic and/or non-enzymatic antioxidant systems are impaired in rheumatoid arthritis (RA) and hence patients are exposed to oxidant stress. This study aimed to establish whether this is really the case. Fasting blood samples were obtained from 24 patients with rheumatoid arthritis and 20 controls. The activities of erythrocyte superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and xanthine oxidase (XO) enzymes and malondialdehyde (MDA), oxidant resistant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 20 publications
11
45
0
2
Order By: Relevance
“…In our study, pMDA and eMDA levels were found to be significantly elevated in the patients with RA compared to controls (Table 1). This is in agreement with other studies in which higher MDA levels have been reported in patients with RA (9,23,24). When we look at this finding with respect to disease activity levels, a significant increase was found in plasma levels of severe RA and erythrocyte levels of moderate and severe RA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, pMDA and eMDA levels were found to be significantly elevated in the patients with RA compared to controls (Table 1). This is in agreement with other studies in which higher MDA levels have been reported in patients with RA (9,23,24). When we look at this finding with respect to disease activity levels, a significant increase was found in plasma levels of severe RA and erythrocyte levels of moderate and severe RA.…”
Section: Discussionsupporting
confidence: 93%
“…However, the relationship of disease activity of RA with erythrocyte activity of SOD and levels of MDA and XO is not clear. Our findings suggested that the levels of eMDA and the activity of eSOD were increased in RA patients, consistent with most of the previous studies (23,32). On the other hand, Banford et al (33) reported a significant decrease in eSOD activity in RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…But possibly increased activity of SOD [35,36] may be attributed to increased O 2 -production by hyperactive cells leading to SOD induction [37,38]. Another possibility may be excessive free radical production through the xanthine-xanthine oxidase system is the primary factors in RA, rather than an impaired antioxidant system [36].…”
Section: Mdamentioning
confidence: 99%
“…Another possibility may be excessive free radical production through the xanthine-xanthine oxidase system is the primary factors in RA, rather than an impaired antioxidant system [36]. Else higher SOD levels may be a change to nullify excessive free radical production.…”
Section: Mdamentioning
confidence: 99%
“…This may be due to higher oxidative stress associated with RA. [16][17][18][19][20] Under the conditions of high levels of oxidants like oxygen free radicals, NO gets converted to injurious peroxynitrite radical (ONOOˉ), which further may get isomerized to NO 3 or get converted to nitrotyrosine [21,22,23]. The low level of NO in RA patients might explain for the relatively high prevalence of vascular pathology such as vasculitis among RA patients.…”
Section: Discussionmentioning
confidence: 99%